Medium Optimization for Penicillin Acylase (PAc) Production by Recombinant B. megaterium MS941 Containing pac Gene from B. thuringiensis BGSC BD1 Using Response Surface Methodology - FENTRI PARAMITHA PUTRI; ASTUTIATI NURHASANAH; NIKNIK NURHAYATI; IS HELIANTI; KHASWAR SYAMSU (Indonesian Society for microbiology, 2015)
Penicillin G acylase (PAc) hydrolyses of the amide bond of benzylpenicillin (Pen-G) releasing PAA and 6-APA, key intermediate in the production of various semisynthetic penicillins. In this study, we optimised the production medium of PAc by RSM using two variables (xylose as inducer and CaCl2 as divalent cations) to obtain the optimum PAc specific activity from Bacillus megaterium btpacBD1. For this purpose, combinations of five different xylose concentrations (0.13 – 0.87 %) and five different CaCl2 concentrations (0.64 – 4.36 mM) were analysed, in a total of 22 experiments. CCD used for the analysis showed that in shake flask cultivations, xylose and CaCl2 showed significant effects on PAc volumetric activity and the quadratic model was in good agreement with the experimental results (R2= 0.86 (p-value < 0.0001)). The maximum specific activity (130.669 ± 50.241 units mg protein-1) was reached when xylose and CaCl2 concentrations were 0.49% and 2.4 mM, respectively, and medium pH was around 7. Under such conditions, the activity of PAc and protein concentration achieved were 1.318 ± 0.406 units mL-1 and 0.0101 ± 0.01 mg mL-1. The shake flask validation experiments demonstrated that with such medium composition the volumetric activity, protein concentration and specific activity achieved were 1.294 ± 0.171 units mL-1, 0.0102 ± 0.0003 mg mL-1 and 125.91 ± 13.309 units mg-1, respectively. When the optimum medium composition was applied in 10 L bioreactor, the optimum volumetric activity (2.0687 ± 0.0820 units mL-1) and protein concentration (0.0078 ± 0.0008 mg mL-1) were achieved 48 h after the start of the cultivation. However, the optimum PAc specific acivity (1260.52 ± 27.5711 units mg protein-1) was achieved 18 h after the start of the cultivation.